КОМУНІКАТИВНИЙ ПОТЕНЦІАЛ ЯК ОСНОВНА СКЛАДОВА КУЛЬТУРИ СПІЛКУВАННЯ МАЙБУТНІХ ВЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2004)
The principal constituents of communicative potential are revealed in the article. The necessity of taking it into consideration while forming communicative culture of future teachers.